MERCURY-ELECTROPLATED PLATINUM-ELECTRODES AND MICROELECTRODES FOR SONOELECTROCHEMISTRY - Lee, C; Compton, R; Eklund, J; Waller, D (1995)
The preparation of mercury-electroplated platinum disc electrodes of both micrometre and conventional dimensions from an aqueous solution of mercury(I) nitrate and potassium cyanide is described. The mercury film electrodes so produced led to very reproducible voltammetric results, as observed by the cathodic reduction of fluorescein to semifluorescein at high pH, both under silent conditions and under ultrasonic irradiation. The electroreduction in the absence of ultrasound is a simple reversible one-electron transfer process (Tafel gradient ∼ 65 mV decade-1). On ultrasonic irradiation an increase in the mass transport-limited current was observed in excess of that expected for a simple one-electron transfer. Possible mechanisms for the electro-reduction in ultrasound are postulated. © 1995.